Simultaneous determination of thermodynamic and kinetic parameters of aminopolycarbonate complexes of cobalt(II) and nickel(II) based on isothermal titration calorimetry data. Issue 4 (25th November 2016) - Tesmar, Aleksandra; Wyrzykowski, Dariusz; Muñoz, Eva; Pilarski, Bogusław; Pranczk, Joanna; Jacewicz, Dagmara; Chmurzyński, Lech
Abstract: The influence of the different side chain residues on the thermodynamic and kinetic parameters for complexation reactions of the Co 2 + and Ni 2 + ions has been investigated by using the isothermal titration calorimetry (ITC) technique supported by potentiometric titration data. The study was concerned with the 2 common tripodal aminocarboxylate ligands, namely, nitrilotriacetic acid and N ‐(2‐hydroxyethyl) iminodiacetic acid. Calorimetric measurements (ITC) were run in the 2‐( N ‐morpholino)ethanesulfonic acid hydrate (2‐( N ‐morpholino) ethanesulfonic acid), piperazine‐ N, N ′‐bis(2‐ethanesulfonic acid), and dimethylarsenic acid buffers (0.1 mol L −1, pH 6) at 298.15 K. The quantification of the metal‐buffer interactions and their incorporation into the ITC data analysis enabled to obtain the pH‐independent and buffer‐independent thermodynamic parameters ( K, Δ G, Δ H, and Δ S ) for the reactions under study. Furthermore, the kinITC method was applied to obtain kinetic information on complexation reactions from the ITC data. Correlations, based on kinetic and thermodynamic data, between the kinetics of formation of Co 2 + and Ni 2 + complexes and their thermodynamic stabilities are discussed. Abstract : Kinetic information on complexation reactions has been obtained using the kinITC method. This method has been used for the first time to study the systems in which the metal ions are involved. Correlations between the kinetics of the complex formation and their thermodynamic stabilities, based on kinetic and thermodynamic data obtained by the ITC, are discussed.